TRAPPING MIKORIZA PADA BERBAGAI JENIS TANAMAN INANG DENGAN BEBERAPA JENIS SUMBER INOKULUM - Nurhayati (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2012)
AbstractThis research aims to study the types of host plants and source of inoculum is best in the manufacture of mycorrhizal biofertilizer. The study was conducted at the home screen Unsyiah Faculty of Agriculture, Soil Biology Laboratory at USU College of Agriculture and Soil Chemistry Laboratory at the Faculty of Agriculture Unsyiah since July 2011 to November 2011. This research used randomized block design (RGD) factorial with two factors and three replications. Factors studied are several types of host plants and some types of sources of inoculum. Variety of host factors consist of A1 = kudzu (Pueraria javanica,) A2 = soybean (Gylice max (L.) Merrill), A3 = corn (Zea mays L.) and factors source of inoculum consisted of B1 = spore origin rhizosfer kudju, B2 = rhizosfer spores from soybean, B3 = spores rhizosfer origin of maize. Parameters observed in this study is the degree of mycorrhizal infection, plant P uptake. From the research results obtained can be concluded that there is interaction between host plant species with the type of source of inoculum of mycorrhizal infectivity and effectiveness. The best treatment of the parameters of the degree of mycorrhizal infection (infectivity of mycorrhizal) and plant P uptake (mycorrhizal effectiveness) is a combination of host plant kudzu to the source of spore inoculum origin rhizosfer kudzu (A1B1).Keyword : mycorrhizal, kudzu, soybean, corn, biofertilizer